Identification of air pollution potential sources through Principal component analysis (PCA) - Abdullah S.; Ismail M.; Ahmed A.N. (IAEME Publication, 2023)
This study intended to determine the air pollution potential sources at different land use of urban, sub-urban and rural areas. Principal Component Analysis (PCA) was utilized in analyzing the meteorological parameters (wind speed, relative humidity, ambient temperature, mean sea level pressure, global radiation, and rainfall amount) and air pollutants data (particulate matter, carbon monoxide, nitrogen dioxide, sulphur dioxide) from year 2010-2014. Result shows that the main contributor is motor vehicles, followed by the influences of meteorology and seasonality. The results can help local authority in managing air quality and controlling the main contributor of air pollution for a better air quality. IAEME Publication.